Workshop Penyusunan Rencana Pembelajaran Matematika Berdiferensiasi untuk Guru Matematika SMP di Kabupaten Jeneponto - Syahrullah Asyari; Muhammad Darwis M.; Agusalim Juhari; Sabri Sabri; Ikhbariaty Kautsar Qadry (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2024)
This community service activity aimed to enhance the skills of mathematics teachers in Jeneponto Regency in designing Differentiated Mathematics Lesson Plans. The workshop was conducted using the Direct Instruction Model and involved 22 teachers from various schools. Participants were provided with theoretical understanding and practical training on instructional strategies responsive to students' varying abilities. The evaluation results showed a significant improvement in the teachers' understanding and skills in designing differentiated lesson plans. However, challenges emerged due to the limited time available for in-depth material exploration. As a result, participants recommended extending the workshop duration and implementing follow-up support. The workshop successfully contributed to the professional development of the teachers, and it is expected that they will continue to apply these skills in their respective schools.